2021
DOI: 10.1038/s41598-020-80145-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in peripheral blood leukocyte transcriptional response to LPS are enriched for HLA region and X chromosome genes

Abstract: Sex-specific differences in prevalence are well documented for many common, complex diseases, especially for immune-mediated diseases, yet the precise mechanisms through which factors associated with biological sex exert their effects throughout life are not well understood. We interrogated sex-specific transcriptional responses of peripheral blood leukocytes (PBLs) to innate immune stimulation by lipopolysaccharide (LPS) in 46 male and 66 female members of the Hutterite community, who practice a communal life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Several studies have shown biallelic expression of the X-encoded TLR7 in females, which results in higher levels of type I interferon induction by plasmacytoid dendritic cells and a greater propensity for immunoglobulin G (IgG) class switching in B cells 40,41 . By contrast, analyses of whole-blood transcriptional responses to LPS found that the vast majority of X-linked genes are commonly induced in both males and females, including the majority of genes known to escape X inactivation 39 . TLR7 may thus represent a unique case, rather than a general rule.…”
Section: Sex and Immune Variationmentioning
confidence: 85%
See 1 more Smart Citation
“…Several studies have shown biallelic expression of the X-encoded TLR7 in females, which results in higher levels of type I interferon induction by plasmacytoid dendritic cells and a greater propensity for immunoglobulin G (IgG) class switching in B cells 40,41 . By contrast, analyses of whole-blood transcriptional responses to LPS found that the vast majority of X-linked genes are commonly induced in both males and females, including the majority of genes known to escape X inactivation 39 . TLR7 may thus represent a unique case, rather than a general rule.…”
Section: Sex and Immune Variationmentioning
confidence: 85%
“…At the level of immune parameters, the most consistently observed associations with sex are altered baseline cellular traits and differential responses to vaccinations 38 . A recent study also found that 47% of HLA class I and II genes showed differences between sexes in expression following stimulation with lipolysaccharide (LPS), a far greater rate than the genome average 39 . While much of the effect of sex is unexplained, the best-studied drivers for this variation are sex chromosomes and sex hormones.…”
Section: Sex and Immune Variationmentioning
confidence: 98%
“…Some of the sex‐dependent activities of LPS could be ascribed to the fact that LPS binds the Toll‐like receptors TLR4 (Lu et al, 2008 ), which are more expressed in male human monocytes and neutrophils (Aomatsu et al, 2013 ; Bannister et al, 2013 ). In this regard, it is relevant to recall that in human leukocytes, 1217 autosomal, 54 X‐linked genes have sex‐specific responses to LPS, as well as 71 autosomal and one X‐linked sex‐specific expression quantitative trait loci (Stein et al, 2021 ), suggesting that LPS activity may occur through multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…5). Sex-specific differences have been further studied during immune activation, in which cells from men and women were exposed to lipopolysaccharide to identify sex-specific responses to microbial stimuli 156 . Interestingly, seven genes in pSS-associated loci showed significant sex by treatment interactions, including four HLA genes, IRF5, OAS1 and IKZF1 (ref.…”
Section: Female Sexmentioning
confidence: 99%